PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA PEMBELAJARAN PKN SD NEGERI 6 PALEMBANG - Tri Meika, Dera; Rizhardi, Rury; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by difficulties in understanding the material, one of which is PKN learning, therefore student learning outcomes are less than optimal and still low. To follow up on this learning problem, it is necessary to take action, one alternative that can be used is to apply the snowball throwing learning model. The purpose of this study was to determine the effect of the snowball throwing model on student learning outcomes in PKN learning. The research method used was the experimental method. The results of this study indicate that the use of the snowball throwing learning model affects student learning outcomes. This is indicated by the results of multiple-choice tests on students in the experimental class where compared to the control class that did not use the snowball throwing model, it was proven by the average score in the experimental class of 73.4 while the average score in the control class students was 67.2 and it can be seen that the significance value of 0.125 <0.05 so that Ho is rejected and Ha is accepted. Thus, it can be concluded that the snowball throwing learning model has an effect on the learning outcomes of students in PKN learning at SD Negeri 6 Palembang.